PROSPECTS FOR SETTLEMENT OF CIVIL CASES THROUGH MEDIATION IN STATE COURTS BASED ON REGULATION OF THE SUPREME COURT NUMBER 1 OF 2016 - Sufmi Dasco Ahmad (Fox Justi : Jurnal Ilmu Hukum, 2021)
The process of examining civil cases (lawsuits) in District Courts, such as at the Class IA Bale Bandung District Court is carried out through several stages, namely from the administrative process, to the examination in front of the trial/trial proceedings, one of which is a peace event (mediation), which carried out at the beginning of the trial, the procedure for which is currently regulated in Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures in Courts, which revokes and declares that Perma Number 1 of 2008, whose implementation is considered ineffective. Based on the background and problems discussed in this thesis, the objectives of this study are as follows: To find out and analyze the process of resolving civil cases through mediation at the Class IA Bale Bandung District Court based on Supreme Court Regulation No. 1 of 2016 concerning Mediation Procedures in Court, and the prospect of settling civil cases through mediation at the Class IA Bale Bandung District Court based on Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures in Court. This study finds answers, namely that: the process of settling civil cases through mediation at the Class IA Bale Bandung District Court based on Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures in Courts has been carried out optimally, but the results of case settlement through mediation have not been achieved optimally and settlement of civil cases through mediation at the Class IA Bale Bandung District Court based on Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures in Courts has good prospects, if judges, mediators, and advocates are able to motivate and encourage litigants to settle the case amicably through mediation in order to accelerate the settlement of the case. In connection with the results of the study, the authors submit the following suggestions: In order for the implementation of the settlement of civil cases through mediation in the District Court based on the Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures in Courts, the results are more optimal, one of which is the need for a mediator who has high integrity and impartiality supported by the ability to listen, ask questions, observe, interview, counsel and negotiate; and it is necessary to socialize the Regulation of the Supreme Court Number 1 of 2016 intensively to all elements of the legal profession to better understand the objectives of the PERMA.